Teatro como acontecimento: The importance of error and of the unfinished in drama education - Calderón Gómez, Juan Carlos (2014)
This reflection includes part of my methodological experience used in my teaching position at the University of Costa Rica. We intend to demonstrate how dramatic pedagogical processes contribute to foster thoughtfulness, playfulness and the awareness of the importance of teamwork.